Calculation of water footprint of the iron and steel industry: a case study in Eastern China. (1st April 2015) - Gu, Yifan; Xu, Jin; Keller, Arturo A.; Yuan, Dazhi; Li, Yi; Zhang, Bei; Weng, Qianting; Zhang, Xiaolei; Deng, Ping; Wang, Hongtao; Li, Fengting
Abstract: China is the largest producer of iron and steel in the world. This heavy industry is characterized by significant water consumption and numerous water-related hazards. In this study, we propose the use of water footprint instead of conventional indicators (fresh water consumption (FWC) per tonne of steel or water consumption (WC) per tonne of steel) for the iron and steel industry. Using an iron factory in Eastern China as an example, we develop a water footprint calculation model that includes direct and virtual water footprints. A system boundary analysis method is then proposed to develop a common and feasible industrial water footprint assessment methodology. Specifically, we analyze the characteristics of the iron and steel industry from a life cycle assessment perspective. A water risk assessment was performed based on the results of the water footprint calculations. The selected iron factory has a water consumption (blue water) footprint of 2.24 × 10 7  m 3, including virtual water, and a theoretical water pollution (gray water) footprint of 6.5 × 10 8  m 3 in 2011, indicating that the enterprise poses a serious risk to the water environment. The blue water and gray water footprints are calculated separately to provide more detailed water risk information, instead of adding these two indicators, which has less environmental significance. Graphical abstract: Highlights: We developed an overall system analysis model to evaluate industry water footprint. We used a Chinese iron factory as case study and made life cycle assessment. We calculated water consumption footprint and water pollution footprint separately. Water footprint is more comprehensive than the current indicators of steel industry. Water footprint can evaluate the water risk of the iron and steel industry.